Inhibition of infective larvae exsheathment and egg hatching of the nematode Haemonchus contortus with extracts of tannin-rich plants - Gomes, Edgard Franco (2013)
The aim of this work was to assess the bioactivity of extracts of the tannin-rich plants Acacia mearnsii, Myracrodruon urundeuva, Caesalpinea bracteosa and Leucaena leucocephala against egg and infective larvae stages of Haemonchus contortus. Two in vitro assays were held: an Egg Hatch Assay (EHA) and a Larval Exsheathment Inhibition Assay (LEIA). The EHA consists of the incubation of previously recovered eggs from infected animal\'s faeces in a solution of plant extract for 24 hours and later differentiation between larvae and nonhatched eggs. The concentrations used were 50.00, 25.00, 12.50, 6.25, 3.12, 1.56, 0.78 and 0.39 mg/mL for A. mearnsii; 1.56, 0.78, 0.39, 0.19, 0.09 and 0.04 mg/mL for M. urundeuva; 6.25, 3.12, 1.56, 0.78, 0.39 and 019 mg/mL for C. bracteosa; and 6.25, 3.12 and 1.56 mg/mL for L. leucocephala. The LEIA consists in the artificial exsheathment of infective larvae, obtained by previous coproculture, after a three hour incubation period with plant extract solution in the concentrations 1,200, 600, 300 and 150 \'mü\'g/mL. The 50 and 99 lethal doses (LD) were calculated for both tests. A dose-dependent effect was found in the two tests, except for L. leucocephala in EHA, where it was not possible to calculate DL50 and DL99 with the chosen doses. The DL50 results for EHA were 0.18, 0.32, and 7.20 mg/mL and for DL99 were 4.31, 5.41, and 187.26 mg/mL, respectively for M. urundeuva, C. bracteosa, and A. mearnsii. For LEIA, the DL50 were 0.40, 0.52, 1.24, and 2.24 mg/mL and for DL99 these were 2.37, 2.28, 19.99 and 2.53 x 103 mg/mL respectively for M. urundeuva, A. mearnsii, L. leucocephala and C. bracteosa. The two highest concentrations of A. mearnsii and the three highest for C. bracteosa were effective (more than 90% of bioactivity); the three highest concentrations of M. urundeuva and the 0.78 mg/mL level of C. bracteosa were moderately effective (between 80 and 90% of bioactivity); the concentrations with low effectiveness (between 60 and 80% of bioactivity) were the 12.50 mg/mL (A. mearnsii), 0.19 mg/mL (M. urundeuva), and 0.39 mg/mL (C. bracteosa); all other concentrations were ineffective (less than 60% of bioactivity). For the LEIA, only the highest dose from A. mearnsii and M. urundeuva were effective; the 600 \'mü\'g/mL were moderately effective and all other doses were ineffective. It should be observed that even if the dose is ineffective against exsheathment, some concentrations were able to significantly delay the process. It was observed that the extracts had bioactivity in vitro within the chosen doses against the hatchability of eggs and exsheathment of larvae of H. contortus, except for L. leucocephala, which was not able to block the hatching of eggs